(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article describes the organization of work on vocational guidance in secondary schools, the theoretical foundations of vocational guidance and a creative approach to it, proposals for professional culture as well.